Use of 3-nitrooxypropanol as feed additive for mitigating enteric methane emissions from ruminants: a meta-analysis. Issue 3 (3rd July 2018) - Jayanegara, Anuraga; Sarwono, Ki Ageng; Kondo, Makoto; Matsui, Hiroki; Ridla, Muhammad; Laconi, Erika B.; Nahrowi,
Abstract: This study aimed to perform a meta-analysis on the effect of 3-nitrooxypropanol (3-NOP) on enteric methane (CH4 ) emissions from ruminants. A total of 12 in vivo studies from 10 articles were integrated into a database. Ruminant species included were dairy cows, beef cattle and sheep. Concentration of 3-NOP in diets varied from 0 to 280 mg/kg dry matter intake (DMI). Parameters included were CH4 emissions, rumen fermentation, microbial population, nutrient digestibility and animal performance. Meta-analysis of data was performed by using mixed model methodology in which different studies were treated as random effects whereas 3-NOP addition levels in diets of ruminants were treated as fixed effects. Results showed that increasing level of 3-NOP addition in diets of ruminants decreased enteric CH4 emissions per unit of body weight, CH4 /DMI, CH4 /milk produced, CH4 /digested organic matter or CH4 /gross energy intake ( p < .05). Production of H2 was higher with increasing level of 3-NOP addition ( p < .001). Addition of 3-NOP decreased total VFA concentration ( p < .01), and decreased and increased proportions of C2 and C3, respectively ( p < .001). Addition of 3-NOP decreased archaea population ( p < .01) but it did not change total bacteria and protozoa populations. The substance had minor effect on digestibility of nutrients. Production performance of dairy cows and beef cattle was limitedly influenced by the addition of 3-NOP in the diets, and it had no negative effect on DMI of ruminants. It is concluded that 3-NOP is an effective feed additive to mitigate enteric CH4 emissions without compromising productive performance of ruminants.